Action Research: Video-assisted Guided Conversation to Enhance Senior Secondary Students’ Speaking Skill - Hidayati, Dewi Syaroh (English Education Department, Universitas Islam Indonesia, 2023)
In reality, many English learners find it difficult to speak and to express their idea in English. Knowing less vocabulary, lack of self confidence, and pronunciation’s error have mostly become the most popular reasons of the students to always keep their briliant ideas to speak. It was proven by the current research at one of senior secondary school in Jember which the students also have the same problems as mentioned above. Therefore, the objective of this research was to enhance senior secondary students’ speaking skill. The researcher employed classroom action research as the research design. This research was conducted at one of senior high schools in Jember, East Java, Indonesia. The data were collected from 18 students in one class and from one cycle of teaching which consisted of five sessions. The cycle covered four stages, including plan, action, observation, and reflection. The result of this research showed that the students’ speaking skills were improved for nineteen percents (19%) after the implementation of video-assisted guided conversation. It was validated by the students’ average score which has improved from sixty seven to eighty. It indicates that the use of video-assisted guided conversation could enhance students speaking skills.